FUNDC1: A Promising Mitophagy Regulator at the Mitochondria-Associated Membrane for Cardiovascular Diseases - Li, Guoyong; Li, Junli; Shao, Ruochen; Zhao, Jiahao; Chen, Mao (Frontiers in Cell and Developmental Biology, 2021)
Abstract Mitochondrial autophagy (or mitophagy) regulates the mitochondrial network and function to contribute to multiple cellular processes. The protective effect of homeostatic mitophagy in cardiovascular diseases (CVDs) has attracted increasing attention. FUN14 domain containing 1 (FUNDC1), an identified mitophagy receptor, plays an essential role during CVDs. Different expression levels of FUNDC1 and its phosphorylated state at different sites alleviate or exacerbate hypoxia and ischemia/reperfusion injury, cardiac hypertrophy, or metabolic damage through promotion or interruption of mitophagy. In addition, FUNDC1 can be enriched at contact sites between mitochondria and the endoplasmic reticulum (ER), determining the formation of mitochondria-associated membranes (MAMs) that regulate cellular calcium (Ca2+) homeostasis and mitochondrial dynamics to prevent heart dysfunction. Moreover, FUNDC1 has also been involved in inflammatory cardiac diseases such as septic cardiomyopathy. In this review, we collect and summarize the evidence on the roles of FUNDC1 exclusively in various CVDs, describing its interactions with different cellular organelles, its involvement in multiple cellular processes, and its associated signaling pathways. FUNDC1 may become a promising therapeutic target for the prevention and management of various CVDs.